The theoretical framework for measuring Key Intangible Performance (KIP) in research and publication using Maqasid al-Shar'iah (MS) - Zakariyah, Luqman; Ali, Mohammed Farid; Ahmad H.Osman, Rahmah; Abdul Rahman, Shukran; Mhd. Sarif, Suhaimi (IIUM Press, International Islamic University Malaysia, 2020)
Application of Maqasid al-Shari'ah to determine and measure the Key Intangible Performance (KIP) in institutional and individual productivity is considered a topical issue in the current era. The shift of emphasis from measuring Key Performance Indicator (KPI) to measuring and quantifying intangible performances is a laudable endeavour. KIP acknowledges the prospective intangible means that contribute to quality productivity of institutions and individuals. Nonetheless, basing the KIP on Maqasid al-ShariÑah is near to none. This article reviews the available literature, in an attempt to develop a theoretical framework for measuring Key Intangible Performance (KIP) in research and publication using Maqasid al-ShariÑah. This paper employs qualitative methodology, which basically relies on textual analysis. This is then combined with Sekaran’s behavioural science operationalization method as a research design to develop a Maqasid based Key Intangible Performance (KIP) measurement framework. The findings show that Research and Publication is essential for the Islamic educational Institutions. It can promote, make impact and integrate Islamic values in contemporary issues. The intangible dimensions are three, preliminaries, regulations & governance, and moral & ethical conducts. All of these correspond to the three levels of maqasid namely, essentials, complements and embellishments.